Molecular mechanism of action of repurposed drugs and traditional Chinese medicine used for the treatment of patients infected with covid-19: a Systematic scoping review - Fui Fui Lem; Fernandes Opook; Dexter Jiunn Herng Lee; Fong Tyng Chee; Fahcina P. Lawson; Su Na Chin (Frontiers Media S.A., 2021)
The emergence of COVID-19 as a pandemic has resulted in the need for urgent development of vaccines and drugs and the conduction of clinical trials to fight the outbreak. Because of the time constraints associated with the development of vaccines and effective drugs, drug repurposing and other alternative treatment methods have been used to treat patients that have been infected by the SARS-CoV-2 virus and have acquired COVID-19.